Isolation and chemical identification of lipid derivatives from avocado (Persea americana) pulp with antiplatelet and antithrombotic activities. Issue 1 (16th October 2014) - Rodriguez-Sanchez, Dariana Graciela; Flores-García, Mirthala; Silva-Platas, Christian; Rizzo, Sheryl; Torre-Amione, Guillermo; De la Peña-Diaz, Aurora; Hernández-Brenes, Carmen; García-Rivas, Gerardo
Abstract : Bioassay-guided isolation of acetogenins from avocado pulp with in vitro antiplatelet aggregation and in vivo antithrombotic effects in CD1 mice. Abstract : Platelets play a pivotal role in physiological hemostasis. However, in coronary arteries damaged by atherosclerosis, enhanced platelet aggregation, with subsequent thrombus formation, is a precipitating factor in acute ischemic events. Avocado pulp ( Persea americana ) is a good source of bioactive compounds, and its inclusion in the diet as a source of fatty acid has been related to reduced platelet aggregability. Nevertheless, constituents of avocado pulp with antiplatelet activity remain unknown. The present study aims to characterize the chemical nature of avocado constituents with inhibitory effects on platelet aggregation. Centrifugal partition chromatography (CPC) was used as a fractionation and purification tool, guided by an in vitro adenosine diphosphate (ADP), arachidonic acid or collagen-platelet aggregation assay. Antiplatelet activity was initially linked to seven acetogenins that were further purified, and their dose-dependent effects in the presence of various agonists were contrasted. This process led to the identification of Persenone-C (3 ) as the most potent antiplatelet acetogenin (IC50 = 3.4 mM) among the evaluated compounds. In vivo evaluations with Persenone A (4 ) demonstrated potential protective effects against arterial thrombosis (25 mg kg −1 of body weight), as coagulation times increased (2-fold with respect to the vehicle) and thrombus formation was attenuated (71% versus vehicle). From these results, avocado may be referred to as a functional food containing acetogenin compounds that inhibit platelet aggregation with a potential preventive effect on thrombus formation, such as those that occur in ischaemic diseases.